SPH Applied to Computational Heat Transfer Problems - Pereira da Silva, Luciano; Meneguette Junior, Messias [UNESP]; Marchi, Carlos Henrique (My University, 2023)
This chapter is intended for the presentation of the numerical simulations that cover all the contents of Chap. 2. In it we show the applications of RRE, as well as AML and discretization using fixed sensor particle. In addition, we show some benchmark solutions for the 1D models of steady and unsteady state heat diffusion